Systemic Risk Definitions and Network Applications in Financial Systems - Hossein Dastkhan (Ihtifaz: Journal of Islamic Economics, Finance, and Banking, 2022)
Introduction: Although the complex financial markets more often lead to moresocial welfare in modern economic systems, they can also cause more severefailures in the case of market downturns. Accordingly, Similar to other complexsystems, financial markets are also exposed to systemic risks. Consideringthe importance of systemic risks in financial markets, we reviewed differentconcepts, definitions, and the related principles of the systemic risk.Purpose: Accordingly, similar to other complex systems, financial markets arealso exposed to systemic risks. Considering the importance of systemic risks infinancial markets, we reviewed different concepts, definitions, and the relatedprinciples of the systemic risk. We also reviewed the main definitions of financialsystemic risk in different aspects.Methodology: To analyze the systemic risks in the financial markets, weintroduce the main approaches of systemic risk analysis and elaborate financialnetwork analysis as one of the main approaches.Findings: The results show that the systemic risk events can be related to thebuildup of small shock on different agents in the financial systems as well asgreat shocks in one or a few numbers of financial agents.